Frequency Response Based Multivariable Feedback Control Design for Transient RCCI Engine Operation. Issue 2 (2020) - Verhaegh, Jan; Kupper, Frank; Willems, Frank
Abstract: Reactivity Controlled Compression Ignition (RCCI) is a high efficient, pre-mixed combustion concept, which is characterized by controlled auto-ignition. RCCI control has to guarantee stable and safe operation for varying operating conditions. Research concentrated on next-cycle fuel path control, so far. However, a crucial step towards on-road implementation is accurate control of both air and fuel path, especially during transients. In this work, a systematic, frequency domain-based design method is presented for coordinated air-fuel path control. Starting from MIMO system identification using Frequency Response Functions, cylinder individual combustion models are developed. Based on these models, a static decoupling matrix and five SISO PI controllers are designed. The followed method allows to analyze and guarantee local robust stability, disturbance rejection and reference tracking properties. For transients, the controller is scheduled as a function of engine speed and torque. The potential of the designed MIMO controller is demonstrated on a six-cylinder Diesel-E85 RCCI engine. This controller shows good reference tracking for engine speed-load variations. Furthermore, it enables safe RCCI operation towards higher loads compared to open-loop control strategies.